Pengelolaan Atraksi Budaya Sebagai Daya Tarik Wisata Sasak Ende Desa Sengkol Kabupaten Lombok Tengah - Lale Yusticia Zachroyana; Alip Suroto; I Gusti Ayu Agung (Jurnal Perhotelan dan Pariwisata, 2026)
Cultural attractions play an important role in strengthening the uniqueness and competitiveness of tourism destinations. Sasak Ende Village, located in Sengkol Village, Central Lombok Regency, represents a traditional Sasak settlement that preserves local cultural values and traditions. The village has significant tourism potential through its traditional houses, cultural performances, and the daily lifestyle of the local community. However, the management of cultural attractions still faces several challenges related to infrastructure, community participation, and tourism promotion. This study aims to analyze the management of cultural attractions in Sasak Ende Village as a tourism attraction and examine its role in increasing tourist interest. The research uses a descriptive qualitative method with data collection techniques including observation, in-depth interviews, documentation, and literature study. Informants in this research consist of tourism managers, local community members, and visiting tourists. The results indicate that cultural attraction management in Sasak Ende Village is implemented through the preservation of traditional houses, cultural demonstrations, handicraft production, and community-based tourism activities. The involvement of local communities plays a crucial role in maintaining the authenticity of Sasak culture. Nevertheless, challenges remain, including limited infrastructure, insufficient promotion, and the need for improved tourism management capacity. This study concludes that effective cultural attraction management combined with community participation and sustainable tourism strategies can enhance the attractiveness of Sasak Ende Village as a cultural tourism destination.